A kind of tamsulosin sustained-release capsule based on quick-dissolving coating and preparation method thereof

By using a methacrylic-ethyl acrylate copolymer dispersion and a modified polyacrylate emulsion as the coating liquid, combined with double bonded sodium carboxymethylcellulose and pentaerythritol triacrylate, the problem of poor performance of coating materials in the prior art was solved, and the stable release and aging resistance of tamsolosin sustained release capsules were achieved.

CN119405627BActive Publication Date: 2025-04-15ANRUOWITA PHARM TAIZHOU CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510024841.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

In the prior art, the aqueous dispersion coating material has problems such as unstable performance release rate, easy cracking of the coating film, easy stickiness and moisture absorption of the product, and degradation of the release performance after storage for a period of time.

Method used

The plasticity, hydrophilicity and transmittance of the coating film are used to improve the drug release rate by adding double bonded sodium carboxymethylcellulose and pentaerythritol triacrylate, thereby improving the drug release rate.

Benefits of technology

The stability of drug release rate and aging resistance are improved, the rupture of the coating film and the uneven release rate are avoided, and the storage stability and release performance of tamsolosin sustained release capsules are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of sustained-release capsules, and specifically discloses a tamsulosin sustained-release capsule based on a quick-dissolving coating and a preparation method thereof; the method comprises the following steps: S1: taking microcrystalline cellulose and talcum powder, mixing to obtain a dry material; adding tamsulosin hydrochloride into water to prepare a drug solution; taking a methacrylic acid-ethyl acrylate copolymer dispersion, adding triacetin and sodium carboxymethyl cellulose, stirring evenly to obtain a granulation dispersion; S2: preparing micropills with the drug solution, the dry material and the granulation dispersion; S3: taking a methacrylic acid-ethyl acrylate copolymer dispersion, adding water, triacetin and a modified polyacrylate emulsion, stirring evenly; adding talcum powder, stirring evenly to obtain a coating solution; coating micropills with the coating solution to obtain coated micropills; S4: taking talcum powder, calcium stearate and coated micropills, mixing, and filling into capsules to obtain tamsulosin sustained-release capsules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sustained-release capsules, and specifically discloses a tamsulosin sustained-release capsule based on a quick-dissolving coating and a preparation method thereof. Background Art

[0002] Tamsulosin hydrochloride is used to treat urination disorders associated with benign prostatic hyperplasia and is slightly soluble in water. In order to improve the taste, reduce adverse reactions, and improve release performance, tamsulosin hydrochloride needs to be coated and made into micropellets before use. Due to the pollution and safety issues of organic solvent coating liquids, the coating materials commonly used in the prior art are water dispersions with better safety, which can be dispersed in water in the form of microparticles, are easy to synthesize, and are environmentally friendly.

[0003] However, the performance of water dispersion coating materials still needs to be improved, such as unstable release rate, easy cracking of the coating film after film formation, easy stickiness and moisture absorption of the product, and a significant decrease in release performance after storage for a period of time. Therefore, it is of great significance to study a fast-dissolving, safe, storage-stable, and release-stable water dispersion-coated tamsulosin micropellets and tamsulosin sustained-release capsules prepared therefrom. Summary of the invention

[0004] The object of the present invention is to provide a tamsulosin sustained-release capsule based on a fast-dissolving coating and a preparation method thereof, so as to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical scheme: A method for preparing tamsulosin sustained-release capsules based on instant coating, comprising the following steps: S1: taking microcrystalline cellulose and talcum powder, mixing to obtain dry materials; adding tamsulosin hydrochloride to water to prepare a liquid medicine; taking methacrylic acid-ethyl acrylate copolymer dispersion, adding triacetin and sodium carboxymethyl cellulose, stirring evenly to obtain a granulation dispersion;

[0006] S2: stirring at a low speed, adding the liquid medicine prepared in step S1 to the dry material prepared in step S1, adding water, stirring and shearing at a low speed, adding half the mass of the granulation dispersion prepared in step S1 within 1 minute, raking, adding the remaining granulation dispersion within 1 minute, stirring evenly, sieving, unloading, and obtaining wet material; adding the wet material to a spheronizer, spheronizing, drying, and granulating to obtain micropellets;

[0007] S3: taking a methacrylic acid-ethyl acrylate copolymer dispersion, adding water, triacetin, and a modified polyacrylate emulsion, and stirring evenly; adding talcum powder, and stirring evenly to obtain a coating solution; using the coating solution to coat the micropellets obtained in step S2, and drying to obtain coated micropellets;

[0008] S4: Take talcum powder, calcium stearate, and the coated pellets obtained in step S3, mix them to obtain composite pellets; fill the composite pellets into capsules (gelatin hollow hard capsules 1#, T / CNPPA3008-2020, locking length 20 mm, content 99.5%) to obtain tamsulosin sustained-release capsules.

[0009] More optimally, by weight: the dry material includes 260-300 parts of microcrystalline cellulose passed through a 40-mesh sieve, and 15-20 parts of talc passed through a 40-mesh sieve; the drug solution includes 0.3-0.5 parts of tamsulosin hydrochloride with a concentration of 0.7-0.75% m / m; the granulation dispersion includes 280-320 parts of methacrylic acid-ethyl acrylate copolymer dispersion, 2.5-3 parts of triacetin, and 2-3 parts of sodium carboxymethyl cellulose.

[0010] More optimally, the coating solution includes the following raw materials, calculated by weight: 8 to 10 parts of methacrylic acid-ethyl acrylate copolymer dispersion, 80 to 90 parts of water, 0.5 to 0.8 parts of triacetin, 3 to 5 parts of modified polyacrylate emulsion, and 0.6 to 1 part of 100-mesh talc.

[0011] More optimally, the composite micro-pellets include the following raw materials, calculated by weight: 6 to 8 parts of talc powder passing through a 100-mesh sieve, and 0.5 to 1 part of calcium stearate passing through a 100-mesh sieve.

[0012] More optimally, the preparation of the modified polyacrylate emulsion includes the following steps: Step 1: uniformly mix citric acid, 3-bromopropylene, sodium carbonate and tetrahydrofuran, stir at 50-60° C. for 3-5 hours, and remove the solvent by post-treatment to obtain a plasticizer;

[0013] Step 2: Mix sodium carboxymethyl cellulose, EDC, NHS, and MES buffer (pH=5.5, 0.1 mol / L) evenly, add amino polyethylene glycol acrylate, react at room temperature for 24-30 hours, and post-treat (pour 1000 parts of ethanol, collect the precipitate by suction, dialyze with deionized water for 3 days with a 12-14 kDa dialysis bag, freeze-dry, and sterilize) to obtain double-bonded sodium carboxymethyl cellulose;

[0014] Step 3: Take sodium dodecyl sulfate and plasticizer, add to water and stir to mix, add methacrylic acid, hydroxyethyl methacrylate, pentaerythritol triacrylate, ethyl acrylate, methyl methacrylate, double-bonded sodium carboxymethyl cellulose, stir evenly, add initiator dropwise under nitrogen protection (the initiator is selected from azobisisobutylamidine hydrochloride V50), react at 70-80°C for 4-6h, adjust the pH to 7-8, filter and purify the material to obtain a modified polyacrylate emulsion.

[0015] More optimally, the plasticizer comprises the following raw materials, by weight: 20-25 parts of citric acid, 10-15 parts of 3-bromopropylene, 10-15 parts of sodium carbonate, and 80-120 parts of tetrahydrofuran; the double-bonded sodium carboxymethyl cellulose comprises the following raw materials, by weight: 2-3 parts of sodium carboxymethyl cellulose, 1.5-2 parts of EDC, 1-1.2 parts of NHS, 200-300 parts of buffer, and 1-1.2 parts of amino polyethylene glycol acrylate; The modified polyacrylate emulsion comprises the following raw materials, calculated by weight: 0.4-0.5 parts of sodium lauryl sulfate, 0.5-0.6 parts of plasticizer, 60-70 parts of water, 10-15 parts of methacrylic acid, 4-6 parts of hydroxyethyl methacrylate, 0.5-0.8 parts of pentaerythritol triacrylate, 10-15 parts of ethyl acrylate, 4-6 parts of methyl methacrylate, 5-8 parts of double-bonded sodium carboxymethyl cellulose, and 0.1-0.15 parts of initiator.

[0016] More optimally, the specific steps for preparing coated micropellets are: preheating the micropellets at 35°C±5°C in a fluidized bed until the LOD is below 1% m / m as measured by an infrared moisture meter, using the Wurster process to control the temperature at 35±3°C, and coating with a coating solution; after the coating spray is completed, drying at 35°C±5°C until the LOD is below 1% m / m as measured by an infrared moisture meter, checking the weight gain after coating to achieve a weight gain of 1.00~1.50% m / m, drying at 40±2°C for 30 minutes, sieving with a 14-mesh sieve, discarding any lumps formed during the process, and obtaining coated micropellets.

[0017] More optimally, the specific steps for preparing micropellets are as follows: add the wet material to a spheronizer with a 900 mm diameter and 3.25 mm mesh plate, operate the spheronizer at a speed of 250 rpm and an atomization pressure of 2.8 bar, spray water tangentially with a 1.5 mm diameter spray gun, spray at a rate of 700-800 g / min, spray for 2-3 min each time, unload, maintain 40°C ± 5°C in the fluidized bed, until the LOD range is 1.0-2.0% m / m measured by an infrared moisture meter, collect the material passing through the 14 mesh sieve and retained on the 30 mesh sieve to obtain micropellets.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a methacrylic acid-ethyl acrylate copolymer dispersion and a modified polyacrylate emulsion are used as main components of a coating solution; when preparing the modified polyacrylate emulsion, a plasticizer containing a double bond and double-bonded sodium carboxymethyl cellulose modified with amino polyethylene glycol acrylate are added; the plasticizer improves the plasticity of the coating film; the sodium carboxymethyl cellulose improves the hydrophilicity of the coating film; and after absorbing water, the coating film swells to improve the permeability of the coating film, thereby improving the drug release rate; the above two components are introduced into the double bond and then connected, thereby improving the affinity with the methacrylic acid-ethyl acrylate copolymer dispersion, thereby avoiding the problems of skin breakage, cracking, poor long-term stability, uneven release rate, etc. caused by poor compatibility; the modified polyacrylate The emulsion also includes pentaerythritol triacrylate to increase film-forming properties and improve the mechanical properties of the film, but adding too much will lead to a decrease in the release rate and a decrease in compatibility with the methacrylic acid-ethyl acrylate copolymer dispersion; the amount of modified polyacrylate emulsion added should not be too much, adding too much will lead to a too fast release rate, resulting in failure to meet the standards, and will cause the coating liquid to be too hydrophilic, and there will still be a trace amount of water in the coating layer after heat treatment. The water continues to evaporate during the subsequent storage period, resulting in a tight coating film, a slow drug release rate, poor aging resistance, and failure to meet the standards; sodium carboxymethyl cellulose is also added to the micropills prepared by the present invention, so that it can swell after absorbing water and improve the release rate, but the amount added should also not be too much, otherwise it will release too quickly and fail to meet the standards. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Unless otherwise specified, the following parts are all parts by mass and percentage by mass;

[0021] Example 1: Preparation of modified polyacrylate emulsion: 22 parts of citric acid, 14 parts of 3-bromopropylene, 12 parts of sodium carbonate and 80 parts of tetrahydrofuran were mixed evenly, stirred at 55° C. for 4 hours, and post-treated to remove the solvent to obtain a plasticizer;

[0022] 3 parts of sodium carboxymethyl cellulose, 1.8 parts of EDC, 1 part of NHS, and 250 parts of MES buffer (pH = 5.5, 0.1 mol / L) were mixed evenly, and 1 part of amino polyethylene glycol acrylate was added, and the mixture was reacted at room temperature for 25 hours, and then post-treated to obtain double-bonded sodium carboxymethyl cellulose;

[0023] Take 0.4 parts of sodium dodecyl sulfate and 0.6 parts of plasticizer, add them to 60 parts of water and stir to mix, add 15 parts of methacrylic acid, 6 parts of hydroxyethyl methacrylate, 0.6 parts of pentaerythritol triacrylate, 12 parts of ethyl acrylate, 4 parts of methyl methacrylate, 6 parts of double-bonded sodium carboxymethyl cellulose, stir evenly, add 0.12 parts of initiator dropwise under nitrogen protection, react at 70°C for 5h, adjust the pH value to 7, filter and purify the material to obtain a modified polyacrylate emulsion;

[0024] Preparation of tamsulosin sustained-release capsules: 276 parts of microcrystalline cellulose passed through a 40-mesh sieve and 16.5 parts of talc passed through a 40-mesh sieve are dry mixed at a low speed of 40 RPM for 10 minutes to obtain a dry material; 0.4 parts of tamsulosin hydrochloride are added to water to prepare a 0.727% m / m drug solution; 300 parts of a 30% methacrylic acid-ethyl acrylate copolymer dispersion L30D-55 are placed in a stainless steel container and filtered with a fine cotton cloth, and 2.7 parts of triacetin and 2.5 parts of sodium carboxymethyl cellulose are added under slow stirring, and stirring is continued for 30 minutes to obtain a granulation dispersion;

[0025] Stir at a low speed of 40RPM, add the liquid medicine to the dry material in 1.5min, add 1.5% water of the liquid medicine weight, keep stirring at a low speed, and shear at a low speed of 1000RPM for 30s, add half of the weight of the granulation dispersion in 1 minute, rake loose, add the remaining granulation dispersion in 1 minute, stir evenly, and discharge the wet material through the discharge port of RMG. The discharge port is equipped with a 6.0mm granulation screen, and the granulation operation speed is medium speed; add the wet material to a mesh screen with a diameter of 900mm and a mesh of 3.25mm In the plate spheronizer SDL900, the spheronization was operated at a speed of 250 rpm and an atomization pressure of 2.8 bar. Water was sprayed tangentially with a spray gun with a diameter of 1.5 mm. The spray rate was 700 g / min. Each spraying lasted for 3 minutes. Unloading was carried out. In the fluidized bed, the temperature was maintained at 40°C and the raking was performed intermittently until the LOD range was 1.0% m / m measured by an infrared moisture meter (under the automatic mode of 105°C). The materials passing through the 14-mesh sieve and retained on the 30-mesh sieve were collected to obtain micropellets.

[0026] 9.2 parts of 30% methacrylic acid-ethyl acrylate copolymer dispersion L30D-55 were placed in a stainless steel container and filtered with fine cotton cloth, slowly stirred, 80 parts of water, 0.6 parts of triacetin, and 4 parts of modified polyacrylate emulsion were added, and stirring was continued for 15 minutes; 0.8 parts of 100 mesh talc were added, and stirring was continued for 30 minutes to obtain a coating solution;

[0027] In the fluidized bed, the pellets were preheated at a product temperature of 35°C until the LOD was 1% m / m as measured by an infrared moisture meter (under 105°C automatic mode), and the coating was performed using the coating solution at a product temperature of 35°C using the Wurster process; after the spraying was completed, the product was dried at a temperature of 35°C±5°C in the fluidized bed until the LOD was 1% m / m as measured by an infrared moisture meter (under 105°C automatic mode), the weight gain was checked to reach 1.2% m / m, and the pellets were dried and cured at a bed temperature of 40°C for 30 minutes, sieved with a 14-mesh sieve, and any lumps formed during the process were discarded to obtain coated pellets; 7.8 parts of talc powder passing through a 100-mesh sieve, 0.78 parts of calcium stearate passing through a 100-mesh sieve, and coated pellets were taken, added to a mixer and mixed for 60 minutes to obtain composite pellets; the composite pellets were filled into capsules to obtain tamsulosin sustained-release capsules.

[0028] Example 2: Preparation of modified polyacrylate emulsion: 22 parts of citric acid, 14 parts of 3-bromopropylene, 12 parts of sodium carbonate and 80 parts of tetrahydrofuran were mixed evenly, stirred at 55° C. for 4 hours, and post-treated to remove the solvent to obtain a plasticizer;

[0029] 2 parts of sodium carboxymethyl cellulose, 1.8 parts of EDC, 1 part of NHS, and 200 parts of MES buffer (pH = 5.5, 0.1 mol / L) were mixed evenly, and 1 part of amino polyethylene glycol acrylate was added, and the mixture was reacted at room temperature for 25 hours, and then post-treated to obtain double-bonded sodium carboxymethyl cellulose;

[0030] Take 0.4 parts of sodium dodecyl sulfate and 0.5 parts of plasticizer, add to 60 parts of water and stir to mix, add 15 parts of methacrylic acid, 4 parts of hydroxyethyl methacrylate, 0.8 parts of pentaerythritol triacrylate, 15 parts of ethyl acrylate, 4 parts of methyl methacrylate, 5 parts of double-bonded sodium carboxymethyl cellulose, stir evenly, add 0.1 parts of initiator dropwise under nitrogen protection, react at 70°C for 6 hours, adjust the pH value to 7, filter and purify the material to obtain a modified polyacrylate emulsion;

[0031] The preparation steps of tamsulosin sustained-release capsules are the same as those in Example 1.

[0032] Example 3: Preparation of modified polyacrylate emulsion: 22 parts of citric acid, 14 parts of 3-bromopropylene, 12 parts of sodium carbonate and 80 parts of tetrahydrofuran were mixed evenly, stirred at 55° C. for 4 hours, and post-treated to remove the solvent to obtain a plasticizer;

[0033] 3 parts of sodium carboxymethyl cellulose, 1.8 parts of EDC, 1 part of NHS, and 300 parts of MES buffer (pH = 5.5, 0.1 mol / L) were mixed evenly, and 1.2 parts of amino polyethylene glycol acrylate were added, reacted at room temperature for 25 hours, and post-treated to obtain double-bonded sodium carboxymethyl cellulose;

[0034] Take 0.5 parts of sodium dodecyl sulfate and 0.6 parts of plasticizer, add them to 60 parts of water and stir to mix, add 15 parts of methacrylic acid, 6 parts of hydroxyethyl methacrylate, 0.5 parts of pentaerythritol triacrylate, 10 parts of ethyl acrylate, 6 parts of methyl methacrylate, 8 parts of double-bonded sodium carboxymethyl cellulose, stir evenly, add 0.1 parts of initiator dropwise under nitrogen protection, react at 70°C for 6 hours, adjust the pH value to 7, filter the material, and obtain a modified polyacrylate emulsion;

[0035] The preparation steps of tamsulosin sustained-release capsules are the same as those in Example 1.

[0036] Comparative Example 1: (Increasing the amount of sodium carboxymethylcellulose added to the granulation dispersion, and the remaining steps are consistent with Example 1) Preparation of tamsulosin sustained-release capsules: 276 parts of microcrystalline cellulose passed through a 40-mesh sieve and 16.5 parts of talc passed through a 40-mesh sieve are dry mixed for 10 minutes under low-speed stirring at 40 RPM to obtain a dry material; 0.4 parts of tamsulosin hydrochloride are added to water to prepare a 0.727% m / m drug solution; 300 parts of 30% methacrylic acid-ethyl acrylate copolymer dispersion L30D-55 are placed in a stainless steel container and filtered with fine cotton cloth, and 2.7 parts of triacetin and 5.5 parts of sodium carboxymethylcellulose are added under slow stirring, and stirring is continued for 30 minutes to obtain a granulation dispersion;

[0037] Stir at a low speed of 40RPM, add the liquid medicine to the dry material in 1.5min, add 1.5% water of the liquid medicine weight, keep stirring at a low speed, and shear at a low speed of 1000RPM for 30s, add half of the weight of the granulation dispersion in 1 minute, rake loose, add the remaining granulation dispersion in 1 minute, stir evenly, and discharge the wet material through the discharge port of RMG. The discharge port is equipped with a 6.0mm granulation screen, and the granulation operation speed is medium speed; add the wet material to a mesh screen with a diameter of 900mm and a mesh of 3.25mm In the plate spheronizer SDL900, the spheronization was operated at a speed of 250 rpm and an atomization pressure of 2.8 bar. Water was sprayed tangentially with a spray gun with a diameter of 1.5 mm. The spray rate was 700 g / min. Each spraying lasted for 3 minutes. Unloading was carried out. In the fluidized bed, the temperature was maintained at 40°C and the raking was performed intermittently until the LOD range was 1.0% m / m measured by an infrared moisture meter (under the automatic mode of 105°C). The materials passing through the 14-mesh sieve and retained on the 30-mesh sieve were collected to obtain micropellets.

[0038] 9.2 parts of 30% methacrylic acid-ethyl acrylate copolymer dispersion L30D-55 were placed in a stainless steel container and filtered with fine cotton cloth, slowly stirred, 80 parts of water, 0.6 parts of triacetin, and 4 parts of modified polyacrylate emulsion were added, and stirring was continued for 15 minutes; 0.8 parts of 100 mesh talc were added, and stirring was continued for 30 minutes to obtain a coating solution;

[0039] In the fluidized bed, the pellets were preheated at a product temperature of 35°C until the LOD was 1% m / m as measured by an infrared moisture meter (under 105°C automatic mode), and the coating was performed using the coating solution at a product temperature of 35°C using the Wurster process; after the spraying was completed, the product was dried at a temperature of 35°C±5°C in the fluidized bed until the LOD was 1% m / m as measured by an infrared moisture meter (under 105°C automatic mode), the weight gain was checked to reach 1.2% m / m, and the pellets were dried and cured at a bed temperature of 40°C for 30 minutes, sieved with a 14-mesh sieve, and any lumps formed during the process were discarded to obtain coated pellets; 7.8 parts of talc powder passing through a 100-mesh sieve, 0.78 parts of calcium stearate passing through a 100-mesh sieve, and coated pellets were taken, added to a mixer and mixed for 60 minutes to obtain composite pellets; the composite pellets were filled into capsules to obtain tamsulosin sustained-release capsules.

[0040] Comparative Example 2: (the amount of modified polyacrylate emulsion added to the coating solution is increased, and the remaining method steps are consistent with Example 1) Preparation of tamsulosin sustained-release capsules: 276 parts of microcrystalline cellulose passed through a 40-mesh sieve and 16.5 parts of talc passed through a 40-mesh sieve are dry mixed for 10 minutes under low-speed stirring at 40 RPM to obtain a dry material; 0.4 parts of tamsulosin hydrochloride are added to water to prepare a 0.727% m / m drug solution; 300 parts of 30% methacrylic acid-ethyl acrylate copolymer dispersion L30D-55 are placed in a stainless steel container and filtered with fine cotton cloth, and 2.7 parts of triacetin and 5.5 parts of sodium carboxymethyl cellulose are added under slow stirring, and stirring is continued for 30 minutes to obtain a granulation dispersion;

[0041] Stir at a low speed of 40RPM, add the liquid medicine to the dry material in 1.5min, add 1.5% water of the liquid medicine weight, keep stirring at a low speed, and shear at a low speed of 1000RPM for 30s, add half of the weight of the granulation dispersion in 1 minute, rake loose, add the remaining granulation dispersion in 1 minute, stir evenly, and discharge the wet material through the discharge port of RMG. The discharge port is equipped with a 6.0mm granulation screen, and the granulation operation speed is medium speed; add the wet material to a mesh screen with a diameter of 900mm and a mesh of 3.25mm In the plate spheronizer SDL900, the spheronization was operated at a speed of 250 rpm and an atomization pressure of 2.8 bar. Water was sprayed tangentially with a spray gun with a diameter of 1.5 mm. The spray rate was 700 g / min. Each spraying lasted for 3 minutes. Unloading was carried out. In the fluidized bed, the temperature was maintained at 40°C and the raking was performed intermittently until the LOD range was 1.0% m / m measured by an infrared moisture meter (under the automatic mode of 105°C). The materials passing through the 14-mesh sieve and retained on the 30-mesh sieve were collected to obtain micropellets.

[0042] 9.2 parts of 30% methacrylic acid-ethyl acrylate copolymer dispersion L30D-55 were placed in a stainless steel container and filtered with fine cotton cloth, slowly stirred, 80 parts of water, 0.6 parts of triacetin, and 8 parts of modified polyacrylate emulsion were added, and stirring was continued for 15 minutes; 0.8 parts of 100 mesh talc were added, and stirring was continued for 30 minutes to obtain a coating solution;

[0043] In the fluidized bed, the pellets were preheated at a product temperature of 35°C until the LOD was 1% m / m as measured by an infrared moisture meter (under 105°C automatic mode), and the coating was performed using the coating solution at a product temperature of 35°C using the Wurster process; after the spraying was completed, the product was dried at a temperature of 35°C±5°C in the fluidized bed until the LOD was 1% m / m as measured by an infrared moisture meter (under 105°C automatic mode), the weight gain was checked to reach 1.2% m / m, and the pellets were dried and cured at a bed temperature of 40°C for 30 minutes, sieved with a 14-mesh sieve, and any lumps formed during the process were discarded to obtain coated pellets; 7.8 parts of talc powder passing through a 100-mesh sieve, 0.78 parts of calcium stearate passing through a 100-mesh sieve, and coated pellets were taken, added to a mixer and mixed for 60 minutes to obtain composite pellets; the composite pellets were filled into capsules to obtain tamsulosin sustained-release capsules.

[0044] Comparative Example 3: (changing the amount of pentaerythritol triacrylate added in the modified polyacrylate emulsion, and the other method steps are consistent with Example 1) Take 0.4 parts of sodium dodecyl sulfate and 0.6 parts of plasticizer, add them to 60 parts of water and stir to mix, add 15 parts of methacrylic acid, 6 parts of hydroxyethyl methacrylate, 1.6 parts of pentaerythritol triacrylate, 12 parts of ethyl acrylate, 4 parts of methyl methacrylate, 6 parts of double-bonded sodium carboxymethyl cellulose, stir evenly, add 0.12 parts of initiator dropwise under nitrogen protection, react at 70°C for 5 hours, adjust the pH to 7, filter and purify the material to obtain a modified polyacrylate emulsion.

[0045] Comparative Example 4: (changing the amount of pentaerythritol triacrylate added in the modified polyacrylate emulsion, and the other method steps are consistent with Example 1) Take 0.4 parts of sodium dodecyl sulfate and 0.6 parts of plasticizer, add them to 60 parts of water and stir to mix, add 15 parts of methacrylic acid, 6 parts of hydroxyethyl methacrylate, 0.2 parts of pentaerythritol triacrylate, 12 parts of ethyl acrylate, 4 parts of methyl methacrylate, 6 parts of double-bonded sodium carboxymethyl cellulose, stir evenly, add 0.12 parts of initiator dropwise under nitrogen protection, react at 70°C for 5 hours, adjust the pH to 7, filter and purify the material to obtain a modified polyacrylate emulsion.

[0046] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: sodium dodecyl sulfate (CAS: 151-21-3); methacrylic acid (CAS: 79-41-4); hydroxyethyl methacrylate (CAS: 868-77-9); pentaerythritol triacrylate (CAS: 3524-68-3); ethyl acrylate (CAS: 140-88-5); methyl methacrylate (CAS: 80-62-6); azobisisobutyramidine hydrochloride V50 (CAS: 2997-92-4); citric acid (CAS: 5949-29-1); 3-bromopropylene (CAS: 106-95-6); sodium carbonate (CAS: 497-19-8); tetrahydrofuran (CAS: 109 -99-9); sodium carboxymethyl cellulose (CAS: 9004-32-4); EDC (CAS: 1892-57-5); NHS (CAS: 6066-82-6); MES buffer (pH = 5.5, 0.1 mol / L); amino polyethylene glycol acrylate (80010113-1000, Tansh); ethanol (CAS: 64-17-5); microcrystalline cellulose (CAS: 9004-34-6); talc (CAS: 14807-96-6); tamsulosin hydrochloride (S40584, Shanghai Yuanye); methacrylic acid-ethyl acrylate copolymer dispersion (30%, L30D-55, Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd.); triacetin (CAS: 102-76-1); calcium stearate (CAS: 1592-23-0).

[0047] Experiment: Take the tamsulosin sustained-release capsules prepared according to the method steps of Examples 1 to 3 and Comparative Examples 1 to 4; refer to the release determination method (Appendix XD Method 1 of Part II of the Chinese Pharmacopoeia 2005 Edition), use the apparatus of the second method of the dissolution determination method, use 900 ml of water as the solvent, the speed is 200 revolutions per minute, sample at the 30th minute, refer to the high performance liquid chromatography method (Appendix VD of Part II of the Chinese Pharmacopoeia 2005 Edition), inject into the liquid chromatograph, record the chromatogram, and calculate the release amount by the peak area according to the internal standard method; the results are as shown in the following table;

[0048]

[0049] Conclusion: The release rate of tamsulosin hydrochloride should be between 5% and 25%; in Comparative Example 1, the amount of sodium carboxymethyl cellulose added in the granulation dispersion was increased, and the swelling rate of the pellets increased after absorbing water, resulting in too fast release and not meeting the standard; in Comparative Example 2, the amount of modified polyacrylate emulsion added in the coating solution was increased, and the release was also too fast and not meeting the standard, and the release rate decreased significantly after being placed for 24 months; in Comparative Examples 3 and 4, the amount of pentaerythritol triacrylate added in the modified polyacrylate emulsion was changed, and the release performance also changed due to the change in the coating component structure, and the performance was not as good as that in the embodiment; in summary, the tamsulosin sustained-release capsules prepared by the present invention have a reasonable release rate and good aging resistance.

[0050] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing tamsulosin sustained-release capsules based on instant coating, characterized in that: The following steps are involved: S1: Take microcrystalline cellulose and talcum powder, mix them to obtain dry materials; add tamsulosin hydrochloride to water to prepare a liquid medicine; take methacrylic acid-ethyl acrylate copolymer dispersion, add triacetin and sodium carboxymethyl cellulose, stir evenly to obtain a granulation dispersion; S2: stirring at a low speed, adding the liquid medicine prepared in step S1 to the dry material prepared in step S1, adding water, stirring and shearing at a low speed, adding half the mass of the granulation dispersion prepared in step S1 within 1 minute, raking, adding the remaining granulation dispersion within 1 minute, stirring evenly, sieving, unloading, and obtaining wet material; adding the wet material to a spheronizer, spheronizing, drying, and granulating to obtain micropellets; S3: taking a methacrylic acid-ethyl acrylate copolymer dispersion, adding water, triacetin, and a modified polyacrylate emulsion, and stirring evenly; adding talcum powder, and stirring evenly to obtain a coating solution; using the coating solution to coat the micropellets obtained in step S2, and drying to obtain coated micropellets; S4: taking talcum powder, calcium stearate, and the coated pellets obtained in step S3, mixing them to obtain composite pellets; filling the composite pellets into capsules to obtain tamsulosin sustained-release capsules; The raw materials of the coating solution are as follows: 8-10 parts of methacrylic acid-ethyl acrylate copolymer dispersion, 80-90 parts of water, 0.5-0.8 parts of triacetin, 3-5 parts of modified polyacrylate emulsion, and 0.6-1 parts of 100-mesh talc; The preparation of the modified polyacrylate emulsion comprises the following steps: step 1: uniformly mixing citric acid, 3-bromopropylene, sodium carbonate and tetrahydrofuran, stirring at 50-60°C for 3-5h, and removing the solvent by post-treatment to obtain a plasticizer; step 2: uniformly mixing sodium carboxymethyl cellulose, EDC, NHS and MES buffer solution with a pH value of 5-6, adding amino polyethylene glycol acrylate, reacting at room temperature for 24-30h, and post-treatment to obtain double-bonded sodium carboxymethyl cellulose; step 3: taking sodium dodecyl sulfate and a plasticizer, adding them into water and stirring and mixing, adding methacrylic acid, hydroxyethyl methacrylate, pentaerythritol triacrylate, ethyl acrylate, methyl methacrylate and double-bonded sodium carboxymethyl cellulose, stirring evenly, dropping an initiator under nitrogen protection, reacting at 70-80°C for 4-6h, adjusting the pH value to 7-8, filtering and purifying the material, and obtaining a modified polyacrylate emulsion; The raw materials of the plasticizer are: 20-25 parts of citric acid, 10-15 parts of 3-bromopropylene, 10-15 parts of sodium carbonate, and 80-120 parts of tetrahydrofuran by weight; the raw materials of the double-bonded sodium carboxymethyl cellulose are: 2-3 parts of sodium carboxymethyl cellulose, 1.5-2 parts of EDC, 1-1.2 parts of NHS, 200-300 parts of MES buffer, and 1-1.2 parts of amino polyethylene glycol acrylate by weight; Calculated by weight, the raw materials of the modified polyacrylate emulsion are: 0.4-0.5 parts of sodium dodecyl sulfate, 0.5-0.6 parts of plasticizer, 60-70 parts of water, 10-15 parts of methacrylic acid, 4-6 parts of hydroxyethyl methacrylate, 0.5-0.8 parts of pentaerythritol triacrylate, 10-15 parts of ethyl acrylate, 4-6 parts of methyl methacrylate, 5-8 parts of double-bonded sodium carboxymethyl cellulose, and 0.1-0.15 parts of initiator.

2. The method for preparing a tamsulosin sustained-release capsule based on a fast-dissolving coating according to claim 1, characterized in that: In terms of mass proportions, the dry material comprises 260-300 parts of microcrystalline cellulose passed through a 40-mesh sieve and 15-20 parts of talc passed through a 40-mesh sieve; the drug solution comprises 0.3-0.5 parts of tamsulosin hydrochloride with a concentration of 0.7-0.75% m / m; the granulation dispersion comprises 280-320 parts of methacrylic acid-ethyl acrylate copolymer dispersion, 2.5-3 parts of triacetin and 2-3 parts of sodium carboxymethyl cellulose.

3. The method for preparing a tamsulosin sustained-release capsule based on a fast-dissolving coating according to claim 1, characterized in that: The composite micro-pellets include the following raw materials, calculated by weight: 6-8 parts of talc powder passing through a 100-mesh sieve, and 0.5-1 part of calcium stearate passing through a 100-mesh sieve.

4. The method for preparing a tamsulosin sustained-release capsule based on a fast-dissolving coating according to claim 1, characterized in that: The specific steps for preparing coated micro-pellets are as follows: preheating the micro-pellets at 35°C±5°C in a fluidized bed until the LOD is below 1% m / m as measured by an infrared moisture meter, using the Wurster process to control the temperature at 35±3°C, and coating with a coating solution; after the coating spray is completed, drying at 35°C±5°C until the LOD is below 1% m / m as measured by an infrared moisture meter, checking the weight gain after coating to achieve a weight gain of 1.00~1.50% m / m, drying at 40±2°C for 30 minutes, sieving with a 14-mesh sieve, discarding any lumps formed during the process, and obtaining coated micro-pellets.

5. The method for preparing a tamsulosin sustained-release capsule based on a fast-dissolving coating according to claim 1, characterized in that: The specific steps of preparing micro-pellets are as follows: add the wet material to a spheronizer with a 900 mm diameter and 3.25 mm mesh plate, operate the spheronizer at a speed of 250 rpm and an atomization pressure of 2.8 bar, spray water tangentially with a spray gun with a diameter of 1.5 mm, and spray at a rate of 700-800 g / min. Each spray is 2-3 minutes, unload, and maintain 40°C ± 5°C in the fluidized bed until the LOD range is 1.0-2.0% m / m measured by an infrared moisture meter, collect the materials passing through the 14-mesh sieve and retained on the 30-mesh sieve to obtain micro-pellets.

6. Tamsulosin sustained-release capsules prepared according to the method for preparing tamsulosin sustained-release capsules based on fast-dissolving coating according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Tamsulosin hydrochloride sustained-release pellet preparation

    CN104586771A

  • Pharmaceutical preparation for oral administration with controlled dissolution rate, the preparation comprising tamsulosin hydrochloride-containing sustained-release pellets

    CN109562072A